2024
DOI: 10.3390/agriculture14020268
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Cassava Clones for Iron, Zinc, and Selenium Biofortification

Karini Aparecida Matos Inacio,
Nancy Carrasco Farfan,
Carlos Eduardo Xisto Azevedo
et al.

Abstract: Cassava (Manihot esculenta Crantz) is a crucial staple food in South America, providing starchy storage roots that contribute to the sustenance of millions. To address deficiencies in iron (Fe), zinc (Zn), and selenium (Se), a global initiative is underway to identify plant species and genotypes that naturally accumulate these nutrients for human consumption, such as cassava. In this way, this study aims to identify potential cassava genotypes for biofortification in Fe, Zn, and Se, while also improving the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…These findings regarding the essential elements surpassed the quantities. (Inacio et al, 2024) despite the different biofortified cassava varieties used in their study compared to ours.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These findings regarding the essential elements surpassed the quantities. (Inacio et al, 2024) despite the different biofortified cassava varieties used in their study compared to ours.…”
Section: Discussionmentioning
confidence: 56%
“…The most common micronutrient deficiencies in cassava include vitamin A, iron (Fe), and zinc (Zn) (Inacio et al, 2024). In this study, variations were observed in the elemental composition of different pro-vitamin A cassava varieties, reflecting slight differences in their genetic makeup.…”
Section: Discussionmentioning
confidence: 66%